Neuropsychology and Advances in Memory Function - B. Gordon (Behavioural Neurology)
Recent developments in the functional and neural bases of several aspects of memory are described including long term cortical memory storage, the transition from immediate to permanent memory mediated by medial temporal structures, working memory, memory retrieval, and implicit memory. These are linked to current data on the nature of anterograde and retrograde amnesia in the degenerative diseases, and also to issues in the clinical diagnosis of memory impairments. Understanding the bases of memory can inform the diagnosis of memory impairments in degenerative diseases, and the patterns of impairment seen in the degenerative diseases can help contribute to knowledge of the mechanisms of normal memory.